Short Communication: The potential of various indigenous Trichoderma spp. to suppress Plasmodiophora brassicae the pathogen of clubroot disease on cabbage - I KETUT SUADA (Society for Indonesian Biodiversity, 2017)
Suada IK. 2017. Short Communication: The potential of various indigenous Trichoderma spp. to suppress Plasmodiophora brassicae, the pathogen of clubroot disease on cabbage. Biodiversitas 18: 1424-1429. On the island of Bali, cabbage (Brassica oleracea L.) is a vegetable that has high economic value especially for farmers who cultivate it as a cash crop. However, the clubroot disease caused by the microbial pathogen Plasmodiophora brassicae decreases its productivity. Much effort has been expended in attempts to decrease the pathogen attack by use of synthetic fungicides, however, this has not had much success; more over such pesticide applications generate environmental pollution. Therefore, biological control using Trichoderma or other organisms antagonistic to the pathogen is an attractive alternative. The purpose of this study was to find, isolate and identify Trichoderma spp. able to decrease the disease incidence and increase plant growth. Twelve indigenous Trichoderma isolates were tested on cabbage plants grown in polybags containing local soil media culture treated with the Trichoderma inocula at a concentration of 1.5x106 CFU per polybag. The results showed that three Trichoderma isolates, i.e. T. hamatum-1, T. harzianum-1, and T. harzianum-2, were able to decrease the clubroot disease and increase cabbage growth as well.